GATS dan Regulasi Nasional Masalah Rekonsiliasi Dua Tujuan dan Kepentingan - Warouw, Adolf (Indonesian Journal of International Law, 2007)
Trade in sevices, far more than trade in goods, is affected by domestic regulations. Many services sectors are highly regulated to ensure a certain level of quality, to protect consumers, environment, public health, or to pursue other social goals. Domestic regulations of all kinds can be drafted and applied in ways that directly or indirectly undermine international trade commitments. Trade rgeime would therefore seem to have legitimate interest in disciplining the use of such regulation. GATS aims at trade liberalization and expansion of trade, hence its central concern is to make sure that national regulation does not create unnecessary barriers that would impede implementation of such objectives. On the other hand, GATS recognizes the rigts of WTO members to regulate and to introduce new regulations on the supply of services in order to meet national policy objectives. The mixed objectives of trade liberalization and national regulation do create potential conflict that leads to the question of what is the main objective of GATS and the role of national regulation. National regulation provides a range of legitimate objectives of multidimensional nature which deserve proper recognition within GATS regime. It requires necessary autonomy and flexibility to respond effectively to social and economic objectives. Multilateral disciplines must therefore be crafted carefully to ensure the appropriate balance between those two opposing objectives.